Prevračanje ledenih gor - Jalen, Gašper (Matrika, 2022)
The capsizing of icebergs is a fascinating natural phenomenon. Finding a stable equilibrium of floating objects is quite complex, even for elementary geometric shapes, despite only accounting for gravitational force and buo- yancy. Derived results are often unintuitive and are predicative of an intriguing impact of the iceberg-capsize on its surroundings.
Keywords: capsizing; floating; icebergs; ledene gore; plavanje; prevračanje; stabilnost; stable equilibrium